A Control Architecture for Time‐Optimal Landing of a Quadrotor Onto a Moving Platform. Issue 5 (27th November 2017) - Hu, Botao; Lu, Lu; Mishra, Sandipan
Abstract: We address the problem of autonomous landing of a quadrotor onto a heaving (moving vertically) platform in this paper. A control architecture that consists of a motion estimation module, a trajectory generation module and a tracking control module is proposed. The motion estimation module estimates the absolute motion of the platform and the quadrotor with the measurements from an on‐board accelerometer and vision measurements. Based on these estimates, the trajectory generation module generates a time‐optimal reference trajectory. With the reference trajectory and motion estimation, the tracking control module synthesizes a control command that enables robust tracking of the reference trajectory. Experimental results and comparison with a state‐of‐the‐art landing controller demonstrate the effectiveness of the proposed control architecture.